A truck dynamics model for driving simulators - Sedran, Stefano (My University, 2016)
Driving simulators provide important opportunities to study interaction between the drivers and vehicle in a wide variety of situations and scenarios. A vehicle dynamics model in the simulator calculates the motion of the simulated vehicle based on the inputs of the driver, in real time. The Swedish National Road and Transport Research Institute (VTI) has a need for an open and in-house developed truck model for its driving simulators. Currently, the truck dynamics models used so far were developed, operated and owned by an OEM. This has obvious restrictions for its use and publicity. This thesis presents the development of a truck dynamics model to be used in the VTI’s driving simulators, keeping the OEM model as a reference. The aim of this project is the development of an open model, with a high level of readability and flexibility for future understanding, modification and use. The model is written in the programming language Modelica in the software Dymola. The chosen strategy is using basic code, even though a library structure is designed. The thesis objective is to investigate the required level of detail for the modelling of trucks for driving simulators. An A-double combination is selected, focusing on the context of normal driving at almost constant speed on dry road. The model complexity is gradually increased, focusing, in each step, on what is believed to be the main contributing phenomena to the trajectory of the vehicle. The model validation consists of two parts. At first, desktop simulations aim at comparing each step of the developed model with the OEM model, using an ISO lane change maneuver. The importance of roll steer, torsional flexibility of the tractor chassis frame, axle dynamics, friction in the fifth wheel, nonlinearity of tyres is investigated. Afterwards, a further comparison is carried out by performing experiments in the VTI’s driving simulator with a few test drivers.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering